Mémoires de champions Corpus des palmarès, d'Octavien à Valentinien Ier - Strasser, Jean-Yves (Bibliothèque des Écoles françaises d'Athènes et de Rome (BEFAR), 2021)
Greek-style artistic and sporting competitions (agōnes) reached a peak, in terms of numbers and geographical coverage, under the Roman High Empire. Musicians, runners and boxers travelled the length and breadth of the Mediterranean world, from Rome to Antioch and from Gaul to Africa, in the hopes of winning the ever-more spectacular prizes on offer. When a monument was erected in honour of a multiple winner of prestigious agōnes, it included, at times, an engraving of the list of his victories as proof of his excellence. The practice of immortalising artistic and athletic careers in stone was most common during the period that spanned from the death of Caesar to the middle of the third century, when this type of engraving stopped almost entirely. This book studies this specific epigraphic genre, based on a corpus of about 270 documents. The lists of victories have their own history, with subtle modifications or surprising major changes, and some also provide an extraordinarily detailed and vivid memory of the champions' lives and their exploits.